Volume 7: Turbomachinery, Parts A, B, and C 2010
DOI: 10.1115/gt2010-22229
|View full text |Cite
|
Sign up to set email alerts
|

Blade Geometry Optimization for Axial Flow Compressor

Abstract: Blade geometry design is crucial for turbomachinery performance and stability. A blade optimization method is developed and presented in this paper. The method consists of several elements: geometry parameterization, numerical simulation of flow and performance, optimization algorithm. Sweep and lean are defined by centroid coordinates of sectional blades while the blade geometry is represented by B-Splines approach, through which deformation of blade shape in terms of sweep and lean can then be readily realiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Besides this, some complex flow phenomena such as the shockwave/boundary-layer interaction and the tip clearance flow in the transonic flow would adversely affect the accuracy of the numerical simulation. A similar underestimation of the aerodynamic performance of Rotor 67 using fine/turbo was also reported in the work of Zheng et al [22]. Figure 7 plots the contour of the relative Mach number under near peak efficiency conditions at the section of 30%, 70%, and 90% spans from the hub.…”
Section: Numerical Methods and Validationsupporting
confidence: 80%
“…Besides this, some complex flow phenomena such as the shockwave/boundary-layer interaction and the tip clearance flow in the transonic flow would adversely affect the accuracy of the numerical simulation. A similar underestimation of the aerodynamic performance of Rotor 67 using fine/turbo was also reported in the work of Zheng et al [22]. Figure 7 plots the contour of the relative Mach number under near peak efficiency conditions at the section of 30%, 70%, and 90% spans from the hub.…”
Section: Numerical Methods and Validationsupporting
confidence: 80%
“…13 It can be seen that the variation trend of numerical result is consistent with the experimental data, which shows the reliability and credibility of the numerical calculation method. After the fan blade static aeroelastic deflection, the overall aerodynamic characteristic 14 Sadeghi and Liu, 15 and Castaneda et al 16 whose results underestimate about 1.2%, 0.75%, and 1.15%, respectively. Fan blade static aeroelastic deflection enhances its capability of channel flow.…”
Section: Resultsmentioning
confidence: 96%
“…The results showed that the Spalart-Allmaras model (SA) and the Shear Stress Transport model (SST) could converge to near stall point and provide the reasonable results. According to the available research works (Zheng et al, 2010;Zhou et al, 2017) based on NASA Rotor 67's simulation by NUMECA/EURANUS. The Spalart-Allmaras was used most as a turbulence model.…”
Section: Methodsmentioning
confidence: 99%